Relationship between number of stegmata on leaf epidermis and anthracnose intensity in Stylosanthes spp. - Jerba, Vanessa de Fátima; Fernandes, Celso Dornelas; Pott, Arnildo (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to quantify the number of stegmata in leaf epidermis of five Stylosanthes species, and correlate it to anthracnose severity. Counting of stegmata number per cell unit was done on paradermal sections stained with 1% saffranine. Anthracnose severity was appraised 12 days after inoculation using isolate of Colletotrichum gloeosporioides. The number of stegmata was similar among the species, except for S. guianensis, which presented lower quantity. Anthracnose severity was higher on S. macrocephala followed by S. capitata. No significant correlation was observed between anthracnose severity and number of stegmata in leaf epidermal cells of the studied species.